Community Assemblies and the Implementation of Local Economic Development Policy in Uganda - Galukande Kiganda, M.; Kabatwairwe, O.; Mzini, L. B. (International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
The study investigated the contribution of Community Assemblies (CA) in the implementation of the Local Economic Development Policy(LED). Two of the core assemblies studied were; Barazas and Neighbourhood Assemblies in Kayonza Sub County, Kayunga district from the period 2012 –2016. The study assessed the role of Barazas in LED and the contribution of Neighbourhood Assemblies in LED. It also identified the factors affecting effectiveness of community spaces in LED. The study used a qualitative descriptive design based on interviews, observations, document and literature review carried out in the district of Kayunga in Kayonza subcounty. Findings indicated that community assemblies play a positive role in the implementation of LED, in the awareness creation, monitoring and evaluation of government programmes, citizen mobilisation, as fora for engagement and introduction of government programmes. Community assemblies were accountability and feedback sharing forums and supported identification of local problems, acted as information centres as well as informed policy changes through recommendations. However, their work was affected by lack of sustainability, politics of public policy, limited citizens’ participation, conflicting policies, poor coordination, human and capital resources, institutional challenges and limited follow up on the concern raised by the citizens through these assemblies. The study recommended participatory planning, coordination, implementation, monitoring and evaluation of government programmes. Similarly, the contribution of community assemblies ought to be recognised and enhanced to realise full economic emancipation, since this is the way to go to recognise an empowered citizenry.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Community Assemblies; Community projects; Local Economic Development; Neighbourhood Assemblies; Economic development